2006
DOI: 10.1515/cclm.2006.227
|View full text |Cite
|
Sign up to set email alerts
|

Biovariability of plasma adiponectin

Abstract: These results demonstrate that plasma adiponectin levels have relatively low biovariability and that adiponectin can be sampled fasting or non-fasting to provide a reliable marker of insulin resistance and incipient type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…Finally, the blood samples of this study were collected under nonfasting conditions. Whereas, this fact appears to have only a negligible impact on the level of adiponectin (45), an association between triglyceride and adiponectin concentrations cannot be evaluated leading to an incomplete picture of the lipid-adiponectin relationship in our patients.…”
Section: Discussionmentioning
confidence: 75%
“…Finally, the blood samples of this study were collected under nonfasting conditions. Whereas, this fact appears to have only a negligible impact on the level of adiponectin (45), an association between triglyceride and adiponectin concentrations cannot be evaluated leading to an incomplete picture of the lipid-adiponectin relationship in our patients.…”
Section: Discussionmentioning
confidence: 75%
“…However, at the time of collection, the samples were ideally treated to limit any influence on stability of samples. The effect of frozen storage on adiponectin levels has to our best knowledge been investigated under a maximum of 30 months, with no discernible effect of mean plasma adiponectin levels being reported (40). We are not aware of any other studies with longer follow-up, but most peptide hormones have been shown to be fairly stable, some peptides even during long-term storage up to 25 years (41).…”
Section: Discussionmentioning
confidence: 99%
“…Although plasma adiponectin levels do not vary markedly over longer periods of time in the absence of significant body weight changes (20), there may be a short-term biovariability. Short-term biovariability has been found to be twofold greater in healthy subjects than in those with the metabolic syndrome (21), and the present study has focused on healthy subjects.…”
Section: Discussionmentioning
confidence: 99%